Sacrality of the Sea: A Contextual Theology of the Sea Meaning in the Cosmology of the Hulaliu Community - Aletheia Christo Pattiasina; Margaretha M.A Apituley; Rolland A Samson (Program Pascasarjana UKIM, 2025)
Environmental degradation, particularly of marine ecosystems, has become a pressing global concern. This is particularly true for the Maluku archipelago, which is deeply connected to the sea. All forms of ecological destruction should be a shared concern, including for the church and its theological perspectives. Using the qualitative method and contextual theology approach, this study explores the cosmological values of the Hulaliu community as a way for Christian theology to contribute meaningfully to sea conservation in Hulaliu. This research also expresses concern about the ecological crisis in the sea at Hulaliu and proposes cosmology as an alternative framework to shift from human-centered thinking toward a more profound care for the sea. The primary result of this research is that people of Hulaliu, in their cosmological idea, emphasize that the sea is more than just a source of livelihood; it is a space where local customs, rules, and social norms are formed. The community’s cosmological view understands the sea and the land as one interconnected whole, offering a form of local wisdom that supports environmental protection, including of forests, land, sea, and the wider ecosystem